Infrastructure resources for clinical research in amyotrophic lateral sclerosis. Issue 1 (May 2013) - Sherman, Alexander V.; Gubitz, Amelie K.; Al-Chalabi, Ammar; Bedlack, Richard; Berry, James; Conwit, Robin; Harris, Brent T.; Horton, D. Kevin; Kaufmann, Petra; Leitner, Melanie L.; Miller, Robert; Shefner, Jeremy; et al.
Abstract Clinical trial networks, shared clinical databases, and human biospecimen repositories are examples of infrastructure resources aimed at enhancing and expediting clinical and/or patient oriented research to uncover the etiology and pathogenesis of amyotrophic lateral sclerosis (ALS), a rapidly progressive neurodegenerative disease that leads to the paralysis of voluntary muscles. The current status of such infrastructure resources, as well as opportunities and impediments, were discussed at the second Tarrytown ALS meeting held in September 2011. The discussion focused on resources developed and maintained by ALS clinics and centers in North America and Europe, various clinical trial networks, U.S. government federal agencies including the National Institutes of Health (NIH), the Agency for Toxic Substances and Disease Registry (ATSDR) and the Centers for Disease Control and Prevention (CDC), and several voluntary disease organizations that support ALS research activities. Key recommendations included 1) the establishment of shared databases among individual ALS clinics to enhance the coordination of resources and data analyses; 2) the expansion of quality-controlled human biospecimen banks; and 3) the adoption of uniform data standards, such as the recently developed Common Data Elements (CDEs) for ALS clinical research. The value of clinical trial networks such as the Northeast ALS (NEALS) Consortium and the Western ALS (WALS) Consortium was recognized, and strategies to further enhance and complement these networks and their research resources were discussed.